Effect of material microstructure on the micro-EDM process - Elkaseer, Ahmed A.; Bigot, Samuel; Surleraux, Anthony; Rosochowski, Andrzej (8th International Conference on MicroManufacturing (ICOMM 2013), 2013)
This paper presents a preliminary experimental study of the factors affecting the micro-EDM process aiming at obtaining a deeper understanding of the micro-EDM die sinking process. In particular, the machining response at micro-scale of materials metallurgically and mechanically modified has been investigated. Tests were conducted that involved producing micro-EDM holes in course grained (CG) Al1070 with an average grain size of 300 m and Ultra Fine Grained (UFG) Al1070 with an average grain size of 0.6 m, produced by Equal-Channel Angular Pressing (ECAP). These experimental trials were carried out under different levels of applied energy, voltage, maximum current and pulse duration in order to identify the effects of these process conditions on the obtainable surface roughness, wear ratio, craters and spark gap. The results of this investigation have revealed that, by refining the material microstructure, a better surface finish can be achieved. This observation can be mainly attributed to the homogeneity of the refined material microstructure that normally leads to more isotropic behavior of the microstructure. Furthermore, the applied energy is found to be the most important factor affecting the roughness average and wear ratio in the micro-EDM process. However, the applied voltage is found to be the second effective factor on wear ratio, while the interaction of energy and current have a significant influence on the surface roughness.
Keywords: surface roughness; craters; gap; micro-EDM; wear ratio; material microstructure